The Influence of Financial Literacy on Financial Behavior and Borrowing Intention from Online Loans/P2P Lending - Garin Pratiwi Solihati; Fitri Indriawati (Technology and Society Perspectives (TACIT), 2026)
This study aims to examine the effect of financial literacy on financial behavior and borrowing intention through peer-to-peer (P2P) lending services, as well as to investigate the mediating role of financial behavior. The study is motivated by the rapid growth of digital lending services, which have expanded access to financial resources while simultaneously increasing potential financial risks, particularly among university students. This research employed a quantitative approach with a causal associative research design. Data were collected through questionnaires distributed to university students with prior experience using P2P lending services and were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that financial literacy has a positive effect on both financial behavior and borrowing intention. Financial behavior also has a positive effect on borrowing intention and partially mediates the relationship between financial literacy and borrowing intention. These findings suggest that improving financial literacy should be accompanied by the development of healthy financial behavior to promote more rational, responsible, and sustainable use of P2P lending services.